Antiseptic negative pressure instillation therapy for the treatment of septic wound healing deficits in oral and maxillofacial surgery - Eckstein, Fabian; Pinsel, Valesca; Wurm, Matthias; Wilkerling, André; Dietrich, Eva-Maria; Kreißel, Sebastian; von Wilmowsky, Cornelius; Schlittenbauer, Tilo (Journal of Cranio-Maxillofacial Surgery, 2019)
Introduction: Impaired wound healing, chronic wounds and extended soft tissue defects present a crucial problem in reconstructive surgery of the head and neck region, even more after radiation therapy. In such cases the standard is a prolonged open wound treatment. The negative pressure instillation therapy might present an alternative therapy option.
CRIS-Team WoS Importer:2019-03-06

Correlation between pain and MRI findings in TMD patients - Wurm, Matthias; Behrends, Tessa; Wüst, Wolfgang; Wiesmüller, Marco; Wilkerling, André; Neukam, Friedrich Wilhelm; Schlittenbauer, Tilo (Journal of Cranio-Maxillofacial Surgery, 2018)
Introduction: Magnetic resonance imaging has been established as the gold standard for assessment of the temporomandibular joint. Apart from an excellent assessment of the soft tissues it has the advantage not to expose the patient to ionizing radiation. There is a lack of literature concerning the correlation between pain intensity and radiological findings of the temporomandibular joint. Moreover there is the question of whether a progressive degeneration of the cartilaginous components is accompanied by an increasing degeneration of the osseous parts of the mandibular joint and vice versa. Therefore, this study aims at analyzing correlations between pain and radiological findings. Furthermore, the link between osseous and cartilaginous degeneration is studied. Materials and methods: 91 patients who attend our outpatient clinic for temporomandibular disorders are included in this prospective study. Apart from a detailed anamnesis and clinical examination - adapted to the Research Diagnostic Criteria for Temporomandibular Disorders -magnetic resonance imaging of both mandibular joints is performed. Pain intensity is measured using the visual analog scale. To assess and grade the radiological findings a classification system is established. The evaluation of the osseous components is based on the classification of osteoarthritis by Kellgren and Lawrence whereas the rating of the cartilaginous components is adapted to the Research Diagnostic Criteria for Temporomandibular Disorders. Correlations are verified by Spearman-Rho. Results: 83,5% of all patients are female. Most of the time, both sides are affected (47.25%). Women state an average pain of 5.7 (+/- 2.4), men 3.5 (+/- 2.5). 182 discs are examined and assessed with our classification system. Most discs (n = 71) show no pathological changes. The majority of patients show no dislocation (n = 104). The most common forms of dislocation are anterior dislocations (n = 51). The majority of patients show no changes in the osseous component (n = 115). Weak to moderate correlations are found between disc and bone degeneration. Moderate to strong correlations are found between left and right TMJ. Conclusions: The classification system which is designed and applied during the study proves to be a reliable and practical Instrument. A standardized evaluation of pathologies concerning the temporomandibular joint is possible by using this system. Numerous patients attending our outpatient clinic do not show any signs of degenerative dysfunctions in the mandibular joints. Degenerations of the osseous components tend to be connected with degenerations of the cartilaginous components and vice versa. The question remains if in the future new procedures in imaging will be able to record pathologies not yet detected. (c) 2018 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
EVALuna2:35087